Social Finance : building bridges to improve lives - Thompson, Kenneth R. (London : SAGE Publications: SAGE Business Cases Originals, 2024)
Social Finance is a recent creation. Begun in the United Kingdom in 2007 and in the United States in 2011, the organization facilitates investments in programs with a goal to support socially responsible outcomes. Social Finance is special because funding is based on the development of quantified outcomes as an essential part of the funding program. The Social Finance concept has been applied in multiple countries and settings with more positive outcomes than typical donation programs because it is linked to clear outcomes rather than contributions without conditions set by a donor. In this case, students will learn about the organization's successes and challenges, culminating in an opportunity to recommend next steps for maximizing positive social impact.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social entrepreneurship -- Case studies; Investments -- Case studies; Finance -- Case studies